Peran Hormon Estrogen Pada Siklus Menstruasi Sebagai Faktor Pemicu Terjadinya Migrain - Vanessa Faradise Inonu (Medula, 2020)
Migraine is a recurrent attacks of headache with signs and symptoms such as nausea, vomiting, photophobia, and phonophobia. Migraine is divided into two subtypes, migraine without aura and migraine with aura. Prevalence of migraine is increase in women after puberty and more than 50% the attack occurs on menstruation. Migrain can be triggered by many factors, such as age, gender, psychologic factors, and the more important is hormonal factor on menstrual cycle, oral contraceptive used, pregnancy, and menopause. However, the menstruation is a significant risk factor in triggering the incidence of migraine without aura. The menstrual cycle consists of three phases, that are the follicular phase, ovulation, and the luteal phase. In the menstrual cycle, there is an important theory that can explain the occurs of menstrual migraine, that is estrogen withdrawal theory that developed by Somerville. The risk of migraine without aura will increase on two days before the menstruation begin until three days of menstruation. This matter is related to estrogen withdrawal or a big decline of estrogen hormone on early follicular phase and late luteal phase. In the presence of estrogen withdrawal, there will be a supressed of serotonergic system and a delayed recovery from the glutamatergic system on central nervous system. The estrogen withdrawal in menstrual cycle which facilitated these neurotransmitter system has a role in triggering the migraine without aura.